2021
DOI: 10.28995/2075-7182-2021-20-16-30
|View full text |Cite
|
Sign up to set email alerts
|

DeepMistake: Which Senses are Hard to Distinguish for a Word­in­Context Model

Abstract: In this paper, we describe our solution of the Lexical Semantic Change Detection (LSCD) problem. It is based on a WordinContext (WiC) model detecting whether two occurrences of a particular word carry the same meaning. We propose and compare several WiC architectures and training schemes, and also different ways to convert WiC predictions into final word scores estimating the degree of semantic change.We participated in the RuShiftEval LSCD competition for the Russian language, where our model achieved 2nd bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For comparability, we use the same model for all the languages. We choose XLM-R (Conneau et al, 2020), a multilingual Transformer-based masked language model which has already been successfully applied to the semantic change detection task (Arefyev and Zhikov, 2020;Arefyev et al, 2021). Although it covers the full linguistic diversity of our data, we additionally fine-tune XLM-R on monolingual diachronic corpora.…”
Section: Introductionmentioning
confidence: 99%
“…For comparability, we use the same model for all the languages. We choose XLM-R (Conneau et al, 2020), a multilingual Transformer-based masked language model which has already been successfully applied to the semantic change detection task (Arefyev and Zhikov, 2020;Arefyev et al, 2021). Although it covers the full linguistic diversity of our data, we additionally fine-tune XLM-R on monolingual diachronic corpora.…”
Section: Introductionmentioning
confidence: 99%
“…In(Arefyev et al, 2021) it was observed that taking more than 100 pairs does not significantly improve the results, though this was observed for a different model.…”
mentioning
confidence: 96%